Kolonisasi Larva Chironomidae pada Substrat Buatan di Perairan Dataran Banjir Sungai Rungan: Pengaruh Kualitas Air - Bambang Sulistiyarto (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
Chironomid larvae can be found in abundance in floodplain waters. This study aimed to determine the influence of water quality parameters on Chironomid larvae colonization on artificial substrates in Rungan river floodplain, Central Kalimantan. This study found 12 species of Chironomid larvae that colonize in artificial substrates : Chironomus, Cricotopus, Dicrotendipes, Microspectra, Polypedilum, Procladius, Tanytarsus, Xenochironomus, Larsia, Macropelopia, Psectrotanypus, and Clinotanypus. Chironomid larvae that colonize ranging from 6533-29568 individu.m-2 with a dry weight of 3.7821 to 16.0845 gram.m-2. Chironomid larvae abundance was positively correlated with water pH, the levels of nitrate, orthophosphate, and negatively correlated with total suspended solids (TSS). Key words : Chironomid larvae, artificial substrates, water quality, floodplain.